Hubungan Motivasi Peternak dengan Adopsi Inovasi pada peternakan babi Rakyat di Kupang Nusa Tenggara Timur: Relationship between Farmer Motivation and Innovation Adoption in Smallholder Pig Farming in Kupang, East Nusa Tenggara - Diana Meliani Sabat; Ni Made Paramita Setyani (Universitas Nusa Cendana, 2023)
Pig farming has great potential for breeding in the city of Kupang, East Nusa Tenggara. The use of pigs as social livestock has led many people to raise pigs. In practice, farmers still rely on traditional habits inherited from their parents and experiences gained from the environment to raise pigs. Efforts are needed to address this. The adoption of innovations is a possible way to improve the productivity of the business, which will have an impact on its progress. The purpose of this research is to analyze the relationship between farmer motivation and the adoption of pig farming innovations. The sample used in this study consisted of 100 pig farmers selected purposively from three districts in the city of Kupang. The analysis used in this study is Spearman's Rank Correlation analysis. The results of the research indicate that there is a very weak, significant, and positive relationship between economic motives and the adoption of innovations, with significance values of 0.019 (economic motives) and correlation coefficients of 0.023. Similarly, there is a very weak, significant, and positive relationship between the utilization of household food waste motive and the adoption of innovations, with a significance value of 0.027 and a correlation coefficient of 0.022. On the other hand, there is a very weak, significant, and negative relationship between socio-cultural motives and the adoption of innovations, with a significance value of 0.085 and a correlation coefficient of -0.019.